W Sprawie Liniowej Teorii Powłok Lepkosprężystych - Bielewicz, E. (Engineering Transactions, 1967)
The paper contains a brief account of the "resolving" equations of the linear problem of isotropic visco-elastic shells subject to the action of an external load and a steady temperature field. In addition to the usual displacement equations and those of the mixed method (for shallowshells) equations for the stress function are represented. The application of these equations has proved to be successful for separating classes of problems for which the state of stress or strain is the same for the visco-elastic and elastic shell.Tensor notation is used for the considerations.